2021
DOI: 10.3390/md19070352
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Daily Kelp (Laminaria japonica) Intake on Body Composition, Serum Lipid Levels, and Thyroid Hormone Levels in Healthy Japanese Adults: A Randomized, Double-Blind Study

Abstract: To investigate whether supplementation with iodine-reduced kelp (Laminaria japonica) powder decreases body fat composition in overweight Japanese subjects, a randomized, double-blind, placebo-controlled intervention study was conducted in 50 Japanese subjects with body mass index (BMI) ≥25 and <30 kg/m2. Subjects were randomly assigned to consume thirty tablets/d (10 tablets orally, 3 times/d) containing either iodine-reduced kelp powder (test, 6 g kelp powder corresponding to 3 g alginate/d) or kelp-free p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 39 publications
1
23
0
Order By: Relevance
“…They reanalyzed the data [ 45 ] and found that phosphatidylcholines with diacyl links, lysophosphatidylcholine/diethanolamine with acyl linkages, and free fatty acids were improved after LJP use. Aoe et al conducted a double-blind clinical trial employing iodine-reduced powder of LJP and found that it significantly reduced the body fat percentage without affecting thyroid function [ 46 ].…”
Section: Resultsmentioning
confidence: 99%
“…They reanalyzed the data [ 45 ] and found that phosphatidylcholines with diacyl links, lysophosphatidylcholine/diethanolamine with acyl linkages, and free fatty acids were improved after LJP use. Aoe et al conducted a double-blind clinical trial employing iodine-reduced powder of LJP and found that it significantly reduced the body fat percentage without affecting thyroid function [ 46 ].…”
Section: Resultsmentioning
confidence: 99%
“…A randomized case-control study for 8 weeks revealed that wakame (Undaria pinnatifida) intake (5 g/day) in brown algae significantly decreased blood pressure and hypercholesterolemia risk in 36 older Japanese individuals with hypertension [36]. A randomized, double-blind, and placebo-controlled intervention that advanced throughout the 8 weeks showed that iodine-reduced kelp (Laminaria japonica) powder supplementation decreased serum LDL-C levels in 50 overweight Japanese adults [37]. Furthermore, in an experimental animal study, the administration of seaweed-protein-derived hydrolysates decreased systolic blood pressure in 20-week-old spontaneously hypertensive rats [38].…”
Section: Discussionmentioning
confidence: 99%
“…A prospective study using meal supplements showed no significant difference in TSH levels between the body fat reduction group and other groups. 13) A controlled follow-up study reported that thyroxine treatment in patients with hypothyroidism increased the resting energy expenditure and decreased body weight, whereas fat mass was unchanged with weight loss, primarily due to the excretion of excess body water. 14) It is well established that thyroid hormone status is correlated with energy expenditure.…”
Section: Discussionmentioning
confidence: 99%